TINJAUAN YURIDIS KEWENANGAN PENJABAT SEMENTARA (PJS) KEPALA DAERAH - Fabian Riza Kurnia; Rizari Rizari (Institut Pemerintahan Dalam Negeri, 2019)
In the Indonesian state administration system, an obligation has been arranged to carry out leave outside the responsibility of the state for regional heads and deputy incumbent regional heads who re-run for the same electoral district. The incumbent regional head's leave obligation causes a vacancy in the position of regional head which affects the stability of governance in the region. The term interim acting (Acting) of the regional head as a public official replacing the regional head and deputy regional head incumbent who carries out campaign leave arises since the issuance of Minister of Home Affairs Regulation Number 1 of 2018. Unlike the definitive regional head elected democratically by the people through the regional head election (Pilkada), filling the vacancy of the leadership of the region through a substitute public official is an administrative mechanism. Because it is not the definitive regional head, not all regional head authority can then be exercised by the acting regional head (Acting) of the regional head.